The Effect of Exercise Volume on Depressive-Related Behaviors and Levels of Brain-Derived Neurotrophic Factor and Serum Testosterone Levels - Torabi, Farnaz; Ahmadi, Reza (International Journal of Sport Studies for Health, 2024)
Objective: The aim of the present study was to investigate the effect of training volume on depression-related behaviors and serum levels of brain-derived neurotrophic factor (BDNF) and testosterone in mice. Male NMRI mice, approximately 80 days old and weighing 20 to 23 grams, were used in this study. Methods and Materials: They were kept under a 12-hour light/12-hour dark cycle at a temperature of 23±1°C, with adequate food and water provided. The male NMRI mice, approximately 80 days old and weighing 20 to 23 grams, were kept under a 12-hour light/12-hour dark cycle at a temperature of 23±1°C, with adequate food and water provided. From 90 days old to 118 days old, the animals underwent swimming exercise for 4 weeks. They were divided into two groups: long-term training volume and short-term training volume. The short-term swimming group included one session of short-term training, while the long-term group included three sessions of long-term training with 10-minute swimming periods and 15-minute rest intervals between each session. The water depth and swimming duration gradually increased from 5 to 15 centimeters (second to fourth week) and from 20 (second to third week) to 30 (fourth week) minutes per day. The non-exercised animals were placed in a round tank without water for a duration similar to that of the exercised animals. Results: The results showed a significant difference in immobility duration between the control group and the two training groups, as well as between the two training groups (P ≤ 0.05). There was also a significant difference in depression levels between the two training groups and between the long-term training group and the control group (P ≤ 0.05). However, there was no significant difference between the short-term training group and the control group (P ≥ 0.05). Post hoc test results indicated a significant difference in BDNF levels between the control group and the long-term training group (P ≤ 0.05). Furthermore, there was a significant difference in testosterone levels between the control group and both the short-term and long-term training groups (P ≤ 0.05), but no difference between the two training groups (P ≥ 0.05). Conclusion: Based on the overall results of the study, different training volumes have varying effects on depression and BDNF levels, with long-term training producing greater effects.